LITTERFALL, LITTER DECOMPOSITION AND NUTRIENT RETURN OF REHABILITATED MINING AREAS AND NATURAL FOREST IN PHANGNGA FORESTRY RESEARCH STATION, SOUTHERN THAILAND - Jetsada Wongprom; Roongreang Poolsiri; Sapit Diloksumpun; Chatchai Ngernsaengsaruay; Samita Tansakul; Wasan Chandaeng (BIOTROPIA, 2022)
Litterfall and litter decomposition play important roles in the maintenance of nutrient cycling and rehabilitation of degraded lands. Litterfall, litter decomposition and nutrient return were investigated in a 27-year-old Acacia mangium plantation on sandy and clay sites, and in a mixed plantation at the Phangnga Forestry Research Station, Phangnga Province, Thailand. Additionally, secondary and primary forests were investigated and compared with the values obtained from the Acacia mangium and the mixed plantations. The results indicated that litter production in A. mangium plantation on sandy and clay sites, and in mixed plantations (15.47, 11.68 and 7.89 t/ha/yr, respectively) was higher than that in the secondary and primary forests (6.34 and 6.92 t/ha/yr, respectively). The rate of litter decomposition was the greatest in the secondary forest (3.01/yr) and the lowest occurred in the primary forest (1.15/yr). The decomposition rate of the mixed leaf litter between native trees and A. mangium in plantations was higher than that of only A mangium leaf, except in the mixed plantations. A high initial nitrogen concentration in A. mangium could accelerate litter decomposition and improve litter quality in the mixed litter. In addition, the nutrient return in plantations was higher than that in the secondary and primary forests, especially for N. Increased litter production, high decomposition rate and nutrient return from A. mangium plantation had important roles in nutrient cycling, suggesting that a mixed plantation consisting of A. mangium and native trees should be considered for the reclamation of mining land.